PENGARUH DIVERSIFIKASI DAN RISIKO BISNIS TERHADAP KINERJA KEUANGAN PERUSAHAAN SEKTOR ANEKA INDUSTRI DI BEI - Turiastini, Mari; Darmayanti, Ni Putu Ayu (E-Jurnal Manajemen; Vol 7 No 1 (2018), 2018)
Assessment of financial performance can be seen from the report of financial statements is how companies manage and allocate resources. The purpose of this study is to explain how the effect of diversification and business risk on financial performance as well as the influence of business risks mediate diversification to financial performance. The sample in this research is manufacturing company miscellaneous industry sector in 2013-2016 which amounts to 14 companies, with sampling technique using purposive sampling. The data has been collected and processed using path analysis technique (Path Analysis). The results of the analysis prove that diversification and business risks have a positive and significant influence on financial performance, diversification has a negative and significant impact on business risk and business risk is not able to mediate the effect diverisifkasi on financial performance. Keywords : diversification, financial performance, business risk.